2021
DOI: 10.1038/s41467-021-25942-4
|View full text |Cite|
|
Sign up to set email alerts
|

Compensatory ion transport buffers daily protein rhythms to regulate osmotic balance and cellular physiology

Abstract: Between 6–20% of the cellular proteome is under circadian control and tunes mammalian cell function with daily environmental cycles. For cell viability, and to maintain volume within narrow limits, the daily variation in osmotic potential exerted by changes in the soluble proteome must be counterbalanced. The mechanisms and consequences of this osmotic compensation have not been investigated before. In cultured cells and in tissue we find that compensation involves electroneutral active transport of Na+, K+, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 101 publications
(183 reference statements)
3
25
0
Order By: Relevance
“…Therefore, the physiological metabolic consequences of losing Nkcc1 in β-cells are potentially related to reduced β-cell mass/volume/size due to dysregulated [Cl – ] i , altered Cl − channel-mediated electrical activity or a combination of both. In fact, inhibition of β-cell Nkcc1 reduced glucose-induced β-cell electrical oscillations modulated by Cl − channels [ 29 , 31 ] whereas isovolumetric circadian oscillations in [Cl – ] i , determined by the activity of Nkcc1 / Kcc , established the frequency of action potential firings in electrically excitable cells [ 95 ]. Regardless of the underlying mechanisms, the age-related metabolic consequences of altered pulsatile/circadian insulin release are multiple [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the physiological metabolic consequences of losing Nkcc1 in β-cells are potentially related to reduced β-cell mass/volume/size due to dysregulated [Cl – ] i , altered Cl − channel-mediated electrical activity or a combination of both. In fact, inhibition of β-cell Nkcc1 reduced glucose-induced β-cell electrical oscillations modulated by Cl − channels [ 29 , 31 ] whereas isovolumetric circadian oscillations in [Cl – ] i , determined by the activity of Nkcc1 / Kcc , established the frequency of action potential firings in electrically excitable cells [ 95 ]. Regardless of the underlying mechanisms, the age-related metabolic consequences of altered pulsatile/circadian insulin release are multiple [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microelectrode arrays were used to record cardiomyocyte local field potentials (hereafter called field potentials), which are extracellular electrical signals generated in part by transient imbalances in ion concentrations in the intercellular space [ 57 59 ]. These field potentials resemble, but are not equivalent to, electrocardiogram recordings, preventing analysis of P, Q, and S waves.…”
Section: Resultsmentioning
confidence: 99%
“…The increased excitability at night can be countered by bumetanide, an inhibitor of the cotransporter NKCC1 that import Cl – in neurons. Although neither studies demonstrated that the observed diurnal change of intracellular Cl – is directly linked to the circadian clock, it is tempting to speculate that the observed changes are, at least to a certain extent, due to the same mechanisms observed in cardiomyocytes ( Stangherlin et al, 2021 ). These data might contribute to explain the dependency of LTP on the time of the day.…”
Section: Circadian Clock Synaptic Plasticity and Cortical Excitabilitymentioning
confidence: 96%
“…This mechanism is suggested by a manifestation of circadian biology that has been known for several years but it has not permeated the neurobiology community yet: during the circadian cycle the intracellular concentration of Na + , K + , Cl − , and Mg 2+ oscillates in phase (Feeney et al, 2016;O'Neill et al, 2020). This process was demonstrated first in non-excitable cells, until a recent beautiful study has demonstrated that the circadian clock causes a periodic change of intracellular K + , Na + and Cl − in cardiomyocytes (Stangherlin et al, 2021). As expected, this process influences cells excitability leading to a diurnal cycle of the frequency of the spontaneous heartbeat that accelerates in correspondence of elevated intracellular Na + and K + .…”
Section: Circadian Clock Synaptic Plasticity and Cortical Excitabilitymentioning
confidence: 99%
See 1 more Smart Citation